Veterinary Forensic Pathology, Volume 2 (Springer International Publishing, 2018)
This richly illustrated two-volume book offers a comprehensive and essential reference guide for veterinary pathologists and clinical veterinarians interested in performing animal necropsies for forensic casework. It presents a broad range of animal crime cases, with particular focus on the post mortem examination and the observed pathology. This second volume guides readers through the forensic evaluation of animal deaths caused by drowning, fire, electrical, and environmental injuries, poisoning, animal fighting, neglect, and sexual abuse. In addition, it offers practical advice on evaluating anesthesia-related deaths, age estimation, and how to write the necropsy report.